2011
DOI: 10.1021/ja2047232
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Syntheses of (−)-Palau’amine, (−)-Axinellamines, and (−)-Massadines

Abstract: Dimeric pyrrole-imidazole alkaloids represent a rich and topologically unique class of marine natural products. This full account will follow the progression of efforts that culminated in the enantioselective total syntheses of the most structurally ornate members of this family: the axinellamines, the massadines, and palau’amine. A bio-inspired approach capitalizing on the pseudo-symmetry of the members of this class is recounted, delivering a deschloro derivative of the natural product core. Next, the enanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
76
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(79 citation statements)
references
References 126 publications
2
76
0
1
Order By: Relevance
“…S6), confirming the correct assignment of its absolute stereochemistry by Fusetani (23) and us (11) previously. Because of our revision of the absolute stereochemistry of ageliferins ( 3 ), 2 and 3 have mismatched absolute stereochemistries.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…S6), confirming the correct assignment of its absolute stereochemistry by Fusetani (23) and us (11) previously. Because of our revision of the absolute stereochemistry of ageliferins ( 3 ), 2 and 3 have mismatched absolute stereochemistries.…”
supporting
confidence: 88%
“…Although oxidation of 6 under neutral or slightly basic conditions proceeded more smoothly, the undesired N -cyclization occurred spontaneously to give the axinellamine skeleton (8). Eventually, we found that oxidation of 6 with N -bromosuccinimide (NBS) proceeded smoothly and cleanly in methanol to give a diastereomeric mixture of massadine-methanol adducts (11). Upon treatment with aqueous HCl, this mixture of oxidation products slowly converted into massadine ( 2a ) (0.014% yield from L-serine) and 3,7- epi -massadine ( 27 ) (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…366 The enhanced reactivity of thioesters toward amine nucleophiles, relative to their corresponding carboxylate esters has also been exploited to prepare complex amide intermediates for natural product synthesis (Figure 56(b) (Figure 57(a)). 368 Alternatively, treatment of a range of methyl ketones (or alcohols) with a mixture of iodine and ammonia results in a tandem Lieben-Haller-Bauer reaction that generates triiodomethylketone intermediates in situ that react with ammonia to afford primary amides (Figure 57(b)). 369 Bode et al have developed a native chemical ligation strategy for amide bond formation using the reaction of α-keto-acids (or isoxazolidines) with hydroxylamines and N-methoxyhydroxylamines, which has proven useful for the synthesis of peptides and proteins (vide infra) (Figures 58(a) and (b)).…”
Section: Phmentioning
confidence: 99%
“…5 Until our report in 2015, 6 there had been only one report of a total synthesis, by Baran s group in 2010, 7 which was followed by the development of an asymmetric version in 2011. 8 The most dif cult challenge in the total synthesis of 1 is the construction of a trans bicyclo[3.3.0]octane system that corresponds to the D/E ring junction, and Baran s group addressed this by adopting a transannular reaction of 9 membered lactam 2, named macro palau amine, leading to 1 in the nal step ( Figure 1a). Despite their short and elegant synthesis of 1, however, the total synthesis of palau amine is still a challenging undertaking.…”
Section: Introductionmentioning
confidence: 99%